2023
DOI: 10.3390/min13070957
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry Tuning Solutions for Flotation of Fine Particles

Abstract: This paper analyses the basic obstacles preventing the fine particles from floating and suggests solutions for the wetting zone between the bubble and the particle during their collision. It has been shown in our recent paper that the basic problem of fine particle flotation is not the low frequency of collisions with the bubbles, but it consists of the efficiency of these collisions. Moreover, there exists a thermodynamic lower size limit for flotation of fine hydrophobized particles in the sub-micron range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Additionally, it was assumed that the sizes of both the bubble and the capillary tube coincided. Our previous results indicated that the bubble-particle attachment efficiency was proportional to the capillary pressure and the size of the bubble [32]. Therefore, the measurements were carried out with the smallest capillary size of 0.5 mm for the fine quartz particles.…”
Section: Bubble-particle Attachment Measurementsmentioning
confidence: 99%
“…Additionally, it was assumed that the sizes of both the bubble and the capillary tube coincided. Our previous results indicated that the bubble-particle attachment efficiency was proportional to the capillary pressure and the size of the bubble [32]. Therefore, the measurements were carried out with the smallest capillary size of 0.5 mm for the fine quartz particles.…”
Section: Bubble-particle Attachment Measurementsmentioning
confidence: 99%